ANALISIS ASPEK BERPIKIR KRITIS DALAM BUKU TEKS BAHASA INDONESIA SMP KELAS VIII - Rahmadani, Suci; Hamsa, Akmal (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2021)
Analysis Of Critical Thinking Aspects In Indonesian Text Book Class VIII Junior High School. This study aims to: (1) describe the form of analysis in the aspect of critical thinking in Indonesian junior high school textbooks for class VIII (2) describe the form of evaluation in the aspect of critical thinking in Indonesian language textbooks for SMP class VIII (3) describe the form of creation in the aspect of thinking critically on Indonesian textbooks for SMP class VIII. This type of research is qualitative research. The results of the study reveal the form of analysis, evaluation, and creation. The form of the analysis consists of three, but there are only two parts, differences and organization, there is no attribution. There is also no coherence activity in the organization. Then in the form of evaluation consists of two, check and critique. However, in the inspection there is still no activity in coordinating. Furthermore, the creation consists of three, but there are only two parts, namely the plan and production, there is no formulation.